Analysis of Feasibility of the Dairy Cattle Business at the Bestcow Company Jember Regency - Wilda Mufarrijah Indah Uhrowiyah; R. Abdoel Djamali (UNEJ e-Proceeding, 2021)
Dairy farming business opportunities in Jember Regency. An active role in supplying fresh cow’s milk to large companies that process fresh cow’s milk. This research aims to find alternatives to the superior potential of agroindustrial dairy development in the Jember Regency. Research design is quantitative research with an expert systems approach. Instruments were used in the form of observations, in-depth interviews with questions that have been compiled in a research questionnaire format. Analytical techniques used are exponential development methods, analytical hierarchy process, and financial feasibility. The following General Geographical Conditions are following the Potential for Livestock Development in Jember Regency. Increasing the superior potential of agroindustry with the support of special cow seedlings, the availability of processing technology, and the needs of business institutional development steps. The contribution of this research is to provide an alternative strategy for the development of the dairy milk business. Keywords: Exponential development methods, Superior potential, Agroindustry, Dairy cow’s milk, Analytical hierarchy process, Financial feasibility